Remaining Life Assessment and Fitness for Service Evaluation of Aging Chemical Reactors in Polyethylene Terephthalate Resin Industry - Munthe, Aditya Pahlawan; Dhaneswara, Donanta; Putra, Wahyuaji Narottama; Widyaputra, Gama (Journal of Materials Exploration and Findings, 2025)
Aging chemical reactors in the polyethylene terephthalate (PET) resin industry require comprehensive evaluation to ensure safe continued operation. This study conducts a remaining life assessment (RLA) and fitness-for-service (FFS) evaluation on five 30-year-old reactors, based on API 510, API 579/ASME FFS-1, and ASME BPVC Section VIII Div. 1 standards. The analysis involves corrosion rate measurement, future corrosion allowance (FCA) projection, and minimum thickness verification. Among the reactors, R-120 was found to have the shortest remaining life less than 15 years. FFS assessments using three criteria Average Measured Thickness, MAWP from Point Thickness Readings, and Minimum Measured Thickness confirm that R-120 meets all safety requirements. The head and shell thicknesses exceed the minimum allowable values; calculated MAWPr values are above the design MAWP; and thicknesses adjusted for FCA remain above 50% of the minimum required. These results indicate that R-120 remains fit for continued service. This study underscores the critical role of standardized assessment and routine inspection in extending the safe operating life of aging process equipment